1986
DOI: 10.1007/bf00291880
|View full text |Cite
|
Sign up to set email alerts
|

The most common fragile site in man is 3p14

Abstract: In man a common fragile site is known to occur at 3p14. We studied the expression of this fragility in a group of 70 normal healthy subjects. Chromosome breaks, chromatid breaks and gaps at 3p14 could be observed in every examined individual, and in a total of 7000 metaphases they were seen in a mean of 4% of cells. Fluorescence studies in ten persons with chromosome No. 3 polymorphism showed that in all cases both Nos. 3 were about equally liable to breakage. A considerable variation in the fra 3p14 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Detailed analysis of the most common fragile site in the human genome, FRA3B in 3p14.2, has revealed frequent breakpoints in this region in cancers, even those with no visible cytogenetic alterations. The FRA7G fragile site, however, has not been characterized in as great detail as FRA3B (Paradee et al, 1995;Wang et al, 1993;Smeets et Kovacs et al, 1988). We have recently shown a clustering of breakpoints in the FRA3B region in pancreatic adenocarcinomas (Shridhar et al, 1996) similar to the observations reported here.…”
Section: Resultssupporting
confidence: 85%
“…Detailed analysis of the most common fragile site in the human genome, FRA3B in 3p14.2, has revealed frequent breakpoints in this region in cancers, even those with no visible cytogenetic alterations. The FRA7G fragile site, however, has not been characterized in as great detail as FRA3B (Paradee et al, 1995;Wang et al, 1993;Smeets et Kovacs et al, 1988). We have recently shown a clustering of breakpoints in the FRA3B region in pancreatic adenocarcinomas (Shridhar et al, 1996) similar to the observations reported here.…”
Section: Resultssupporting
confidence: 85%
“…However, whether or not fragile sites play a causative role in these structural chromosome alterations has yet to be determined. FRA3B, at chromosome band 3p14.2, is the most highly inducible fragile site in the human genome (Smeets et al, 1986). The constitutive familial renal cell carcinoma-associated translocation t(3;8)(p14.2;q24) (hRCC) (Cohen et al, 1979) was localized immediately centromeric of FRA3B (Paradee et al, 1995;Boldog et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed most unstable site was found at BAC 14 (RP11-48E21), which contains exon 5 with the start codon of the FHIT gene , making it temping to speculate that deletions in exon 5 may account for reduced expression of the FHIT proteins seen in DLBCL cases (Chen et al, 2004). This frequent region of loss also matches a human common fragile site, FRA3B (Smeets et al, 1986). FRA3B is the most highly fragile site in the human genome, in which unstable sequences with repeats and transposons are included (Huebner and Croce, 2001).…”
Section: Discussionmentioning
confidence: 99%